WAQF MANAGEMENT BY ISLAMIC BOARDING SCHOOLS FOR ECONOMIC INDEPENDENCE OF MUSLIM COMMUNITIES: A CASE STUDY OF PERSIS IN WEST JAVA - Jaenudin, Jaenudin; Saepullah, Usep; Hidayat, Agi Attaubah (Al-Muamalat: Jurnal Ekonomi Syariah, 2021)
Waqf is a crucial institution in Islamic social practices utilised for community welfare since the era of Prophet Muhammad (peace be upon him). Initially, waqf primarily consisted of immovable assets, such as agricultural land, as Umar ibn Khattab's waqf demonstrated. In Islamic law, waqf has distinct legal characteristics that set it apart from zakat, infaq, sadaqah, and hibah, even though they share similarities in material nature. Over time, the scope and management of waqf have evolved, particularly in Islamic boarding schools (pesantren), which leverage waqf to foster economic independence for the Muslim community. This study explores waqf management within Persatuan Islam (Persis) pesantren in West Java, focusing on its regulatory framework, implementation, and distribution of benefits. The findings indicate that waqf management within Persis adheres to structured guidelines, as outlined in the Kaifiyat Kerja and Pedoman Jam'iyyah Persatuan Islam (2011). Waqf management in Persis pesantren is carried out independently, with pesantren acting as both managers (nadzir) and implementers. The distribution of waqf benefits is predominantly directed toward social and educational initiatives. However, efforts to expand its role in developing broader economic independence require further collaboration with economic actors to fully realise the potential of waqf in supporting the community's welfare.